Effects of Group Awareness and Self-Regulation Level on Online Learning Behaviors - Lin, Jian-Wei; Szu, Yu-Chin; Lai, Ching-Neng (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
Group awareness can affect student online learning while self-regulation also can substantially influence student online learning. Although some studies identify that these two variables may partially determine learning behavior, few empirical studies or thorough analyses elucidate the simultaneous impact of these two variables (group awareness and self-regulation) on online learning behavior. This paper compared one online collaboration environments with GA support with one without group awareness (NA) support and further investigated how these two variables, different system types (i.e., GA and NA) and different self-regulation levels (i.e., high and low), influence learning task (i.e., assessment) participation, and peer interaction (i.e., asking for help and willing to help) using two-way analysis of variance (ANOVA). Analytical results first showed that both variables have significant interaction on assessment participation and requesting rate. GA can particularly stimulate students with high-level self-regulation to engage more learning task (assessment) participation and ask for help more, compared with students with low-level self-regulation. Second, both variables have no significant interaction on willingness to help. The GA class can enhance a student’s willingness to help regardless of his/her self-regulation level.